Electronic Structure of Tungsten-Doped β-Ga2O3 Compounds. (1st January 2019) - Zade, Vishal; Mallesham, B.; Roy, Swadipta; Shutthanandan, V.; Ramana, C. V.
Abstract : Tungsten (W) doped gallium oxide (Ga2 O3 ) (Ga2-2 x W x O3, 0.00≤ x ≤0.30, GWO) polycrystalline ceramic compounds were synthesized via conventional, high-temperature solid-state reaction method. The effect of W-doping on the crystal structure and electronic structure of the resulting GWO materials is studied in detail. The GWO compounds were single-phase, crystallized in β -Ga2 O3 for x ≤0.15, at which point the Ga2 O3 -WO3 composite formation occurs. The average crystallite size increases with increasing W-content; however, the effect is predominant only in the single phase GWO compounds. Corroborating with structural analyses, the X-ray photoelectron spectroscopy (XPS) measurements reveal the chemical state of W ions vary in GWO compounds as a function of W concentration. The mixed chemical valence states of W (W 4+ and W 6+ ) were evident in single-phase GWO compounds where the W-concentration is lower. However, W ions exhibit the highest chemical valence state (W 6+ ) for higher x values, which resulted in the Ga2 O3 -WO3 composite formation. The Ga ions exists in their highest chemical valence state (Ga 3+ ) in all of the GWO compounds. The scientific understanding of the electronic structure of the GWO materials derived as function of W concentration could be useful while considering the W-doped Ga2 O3 materials and/or W-Ga2 O3 contacts for electronic and optoelectronic device applications.